The Influence of Product Quality, Live Shopping Service Quality, and Consumer Trust on Wardah Product Purchasing Decisions by Generation Z - Jovanka Rizki Utami; Widarta Widarta (Arthatama: Journal of Business Management and Accounting, 2025)
This study aims to analyze the influence of product quality, live shopping service quality, and consumer trust on Wardah product purchasing decisions by Generation Z through the Shopee e-commerce platform in Yogyakarta. In the digital context, consumer trust, in addition to product quality, is a key factor in determining online purchasing behavior. This study used a quantitative approach with 100 respondents selected through a purposive sampling technique. The research instrument was a closed-ended questionnaire with a five-point Likert scale, and the data were analyzed using multiple linear regression. The results showed that product quality and consumer trust had a significant partial effect on purchasing decisions, while live shopping service quality had no significant effect. However, simultaneously, the three variables had a significant effect with an Adjusted R² value of 0.603, meaning 60.3% of the variation in purchasing decisions can be explained by this model. These findings emphasize the importance of a holistic approach in digital marketing strategies, emphasizing product quality, building trust, and increasing the effectiveness of live shopping services to encourage consumer loyalty in the e-commerce era.